Inovasi Penilaian dalam Pembelajaran Terjemah Arab-Indonesia - Mikyal Kaisa Rasyid (ALSYS, 2026)
Assessment in Arabic-Indonesian translation learning in higher education is still often characterized by teacher subjectivity and the absence of standardized evaluation standards. An assessment focus that tends to be fixed on the final product without considering students’ cognitive processes causes evaluation to be less optimal in supporting the improvement of translation competence. This study aims to formulate and develop an innovative translation assessment rubric design model that is more objective, systematic, and learning-oriented. This study used a qualitative method with a library research approach through critical analysis of various primary and secondary literature related to contemporary translation theory and educational evaluation. The results of the study produced the concept and design of an analytical assessment rubric model that proportionally integrates three main dimensions, namely accuracy of meaning, translation equivalence, and language fluency. The conclusion of the study affirms that the implementation of a comprehensive analytical rubric can minimize teacher subjectivity bias while also functioning as an assessment instrument for learning. The implications of this study provide theoretical contributions to the development of studies on Arabic-Indonesian translation learning evaluation, as well as practical implications for teachers in providing constructive formative feedback to continuously improve students’ translation competence.